The Moving of Seaport from Labuhan Deli to Belawan in the Period of 1863-1942 - Suprayitno Suprayitno; Ratna Ratna; Rohani Rohani; Ganie Ganie; Handoko Handoko (Budapest International Research and Critics University, 2020)
Plantation economic growth has the impact on development in various aspects. One of them is shipping and trade development. Before the existence of plantations in East Sumatera, shipping and trade in Medan were centered at Labuhan Deli as a river-port. Since big ships could not sail on the river, it was considered not effective and efficient anymore. Therefore, the Dutch Colonial Government planned to build a seaport located on the sea coast so that loading and unloading would be easy to do, and they selected Belawan to be the new seaport. The research problems were how about the existence of Labuhan Deli by the policy of the Dutch Government on moving the seaport to Belawan and what was their reason for it, and how about shipping and trade business in Belawan. This research used archives and other writing materials from the period of the Dutch Colonial Government in Medan and used historical method. The objective of the research was to find out whether plantation economic condition could change various aspects, including shipping and trade at the time. The result of this research was expected to become the reference for the writing on advanced maritime history, particularly on seaport.